Lithium supplement material and preparation method and application thereof

By adopting a lithium supplementary material with a double-layer core-shell structure and using the coating technology of amorphous carbon and MOF materials, the problems of low energy density of lithium iron phosphate batteries and poor stability of lithium supplementary materials are solved, and the energy density and circulation performance of lithium batteries are improved.

CN119725459APending Publication Date: 2025-03-28EVE POWER CO LTD

Patent Information

Application Number
CN202411915604.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The energy density of lithium iron phosphate batteries is low, and there are safety risks and processing difficulties in the negative electrode lithium supplementation, which has led to the positive electrode lithium supplementation becoming the main way to increase the energy density. However, the residual alkali content of lithium supplementation materials is high, which is easy to react with air, resulting in the formation of gel and reduces electron conductivity.

Method used

The lithium supplement material adopts a double-layer core-shell structure. The first shell layer is composed of amorphous carbon and the second shell layer is MOF material. The electronic conductivity and stability of the lithium supplement material are improved by coating the carbon material and MOF material to isolate carbon dioxide and water in the external environment.

Benefits of technology

The electronic conductivity and stability of lithium supplement materials are significantly improved, gel formation is avoided, and the energy density and circulation performance of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725459A_ABST
    Figure CN119725459A_ABST
Patent Text Reader

Abstract

The invention specifically discloses a lithium supplementing material and a preparation method and application thereof. The lithium supplementing material comprises a lithium supplementing agent inner core, and a first shell layer and a second shell layer which are sequentially arranged away from the surface of the lithium supplementing agent inner core, the first shell layer comprises a carbon material, and the second shell layer comprises an MOF material. The method has the advantage of improving the energy density and the cycle performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium supplement material and a preparation method and application thereof. Background Art

[0002] As lithium-ion batteries are used more and more in the field of power vehicles, the performance requirements for lithium batteries are also getting higher and higher. Lithium iron phosphate batteries are gradually attracting attention due to their advantages such as long life and high safety performance. However, lithium iron phosphate batteries also have certain disadvantages, namely, the energy density of lithium iron phosphate batteries is relatively low. Generally, the energy density of a single cell is only about 160Wh / kg.

[0003] In response to the above problems, pre-lithiation technology is currently used to improve the energy density of lithium iron phosphate batteries; by selecting appropriate lithium supplement materials, the energy density of single cells can be increased to 170Wh / kg, or even 180Wh / kg. Pre-lithiation technology is mainly divided into two methods: positive electrode lithium supplement and negative electrode lithium supplement. However, negative electrode lithium supplement has greater safety risks and processing difficulties. Therefore, in practical applications, positive electrode lithium supplement is generally used to improve the energy density of lithium iron phosphate batteries. Specifically, positive electrode lithium supplement generally involves adding an appropriate amount of lithium supplement material to the positive electrode active material during the homogenization process to obtain a positive electrode active material containing the lithium supplement material. These excess lithium elements are released from the positive electrode active material during the charging process and embedded in the negative electrode to supplement the irreversible capacity of the first charge and discharge.

[0004] However, due to the high residual alkali content of the lithium-supplementing material, it is easy to react with carbon dioxide and water in the air to generate hydroxide, and then react with the binder in the positive electrode active material, causing the positive electrode active material to gel during the slurry process, reducing the electronic conductivity of the lithium-supplementing material, and is not conducive to improving the energy density and cycle performance of the lithium battery. Summary of the invention

[0005] In order to avoid the gel problem that occurs after the lithium supplement material is added to the positive electrode active material and to improve the electronic conductivity of the lithium supplement material, the present application provides a lithium supplement material and a preparation method and application thereof.

[0006] In the first aspect, the present application provides a lithium supplement material, which adopts the following technical solution:

[0007] A lithium supplement material comprises a lithium supplement core and a first shell layer and a second shell layer sequentially arranged on a surface away from the lithium supplement core; the first shell layer comprises a carbon material, and the second shell layer comprises an MOF material. MOF materials, also known as metal organic framework materials, are a class of compounds formed by the coordination of metal ions or metal clusters with organic ligands to form a one-dimensional, two-dimensional or three-dimensional structure.

[0008] First, the present application forms a first shell layer composed of amorphous carbon on the surface of the lithium supplement core by coating the carbon material on the surface of the lithium supplement core, and the carbon source is subjected to high temperature treatment under oxygen-deficient conditions to form a network of amorphous carbon, thereby forming a first shell layer composed of amorphous carbon layers on the surface of the lithium supplement core, and the first shell layer is tightly bonded to the lithium supplement core, the coating thickness is uniform, the coating is flat, and it is not easy to fall off. While isolating the lithium supplement core from carbon dioxide and water in the external air, an overall conductive network layer is formed, which significantly improves the electronic conductivity of the lithium supplement material; second, the amorphous carbon layer in the first shell layer has a tight bonding strength with the MOF material, thereby improving the coating stability of the first shell layer and the second shell layer; and effectively inhibits the crystal growth of particles during high-temperature treatment, inhibits particle agglomeration Polymerization is conducive to the formation of uniform and controllable micron- or nano-scale particles, thereby reducing the migration path of electrons and lithium ions and improving the lithium replenishment performance and electrochemical performance of lithium replenishment materials; thirdly, the framework structure of the MOF material in the second shell can construct a regular and orderly pore structure, which is conducive to the migration of ions and electrons, and the framework structure can alleviate the volume expansion of the positive electrode during the use of the lithium battery and improve the cycle performance of the lithium battery; more importantly, the MOF material in the second shell can actively capture carbon dioxide in the external environment and "fix" it in its metal structure framework, further isolating the reaction between the lithium replenisher core and carbon dioxide and water in the external environment, and significantly improving the cycle performance of the lithium battery.

[0009] In the present application, the lithium supplement agent core is coated by the first shell layer and the second shell layer, which significantly improves the chemical stability of the lithium supplement material while not reducing its conductivity due to the insulating effect of the coating layer, so that the lithium supplement performance of the lithium supplement material can be exerted for a long time, thereby improving the energy density and cycle performance of the lithium battery.

[0010] Optionally, the particle size D50 of the lithium supplementing material is 5-15 μm, for example, 5 μm, 7 μm, 9 μm, 10 μm, 11 μm, 13 μm, 15 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0011] The lithium supplement material prepared in the present application has regular ion and electron transmission channels, which improves the ion conductivity of the lithium supplement material and significantly improves the stability of the lithium supplement material.

[0012] Optionally, the thickness of the first shell layer is 1-10 nm, for example, 1 nm, 3 nm, 5 nm, 6 nm, 8 nm, 9 nm, 10 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Optionally, the thickness of the second shell layer is 10-50 nm, for example, 10 nm, 18 nm, 25 nm, 32 nm, 38 nm, 45 nm, 50 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] By controlling the thickness of the first shell and the second shell, since the MOF material in the second shell has a more regular crystal structure and pores suitable for lithium ion and electron transmission compared to the amorphous carbon in the first shell, when the thickness of the second shell is high, the ion transmission performance and electronic conduction performance of the lithium supplement material can be significantly improved, thereby improving the conductivity of the lithium battery.

[0015] Optionally, the MOF material includes any one of Al-MOF, Nb-MOF, Ti-MOF, and Mg-MOF.

[0016] Optionally, the lithium supplement core includes at least one of lithium-rich lithium iron oxide, lithium-rich lithium nickel oxide, lithium-rich manganese-nickel oxide, and lithium-rich nickel-iron oxide.

[0017] In a second aspect, the present application provides a method for preparing a lithium supplement material, using the following technical solution:

[0018] A method for preparing a lithium supplement material comprises the following steps:

[0019] Step 1: After mixing the lithium source, the iron source and the carbon source, adding water and grinding to obtain a pre-ground slurry; preferably, the molar ratio of the lithium element, the iron element and the carbon element in the pre-ground slurry is (5.5-7):1:(3-4), for example, it can be 5.5:1:3, 5.5:1:4, 7:1:3, 7:1:4, 6:1:3.5, 6:1:3, 6:1:4, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable; preferably, the particle size D50 of the particles in the pre-ground slurry is 0.2-1 μm, for example For example, it can be 0.2 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, and lithium acetate; the iron source includes at least one of ferrous sulfate, ferric phosphate, and ferric oxide; the carbon source includes at least one of polyethylene glycol PEG, lactose, and fructose; preferably, the mixing method adopts any one or a combination of ball milling, grinding, spraying, stirring, and ultrasound;

[0020] Step 2, granulating the pre-ground slurry to obtain a first precursor; the particle size D50 of the first precursor is 1-10 μm, for example, it can be 1 μm, 3 μm, 4 μm, 5 μm, 7 μm, 8 μm, 10 μm, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; preferably, the particle size D50 of the first precursor is 5-6 μm, for example, it can be 5 μm, 5.2 μm, 5.4 μm, 5.5 μm, 5.7 μm, 5.9 μm, 6 μm, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable;

[0021] Step three, spraying the first precursor with the atomized MOF material, and drying to obtain a second precursor; the drying temperature in the step three is 70-105°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 100°C, 105°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0022] Step four, calcining the second precursor to obtain the lithium-replenishing material; during the calcination process of the step four, the temperature is increased at a rate of 2-10°C / min, for example, it can be 2°C, 3°C, 5°C, 7°C, 8°C, 9°C, 10°C, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The lithium-replenishing material is obtained by constant temperature calcination at 500-800°C for 10-18h, for example, the calcination temperature can be 500°C, 600°C, 650°C, 700°C, 800°C, and the calcination time can be 10h, 12h, 14h, 15h, 17h, 18h, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0023] In the process of preparing the pre-ground slurry in step 1 of the present application, a carbon source is added. The carbon source can be evenly dispersed in the first precursor prepared by the pre-ground slurry. In the subsequent sintering process, the carbon source can act as a barrier between the particles, thereby slowing down the growth of primary particles and avoiding the growth into large single crystal particles, which is beneficial to improving the conductivity of the material.

[0024] In the step three, the preparation of the atomized MOF material includes the following steps: mixing the MOF material and ethanol and grinding them to obtain MOF slurry, wherein the solid content of the MOF slurry is 1%-10%, for example, it can be 1%, 3%, 5%, 6%, 8%, 10%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] By controlling the solid content of the MOF slurry, the present application can improve the coating uniformity of the MOF slurry on the surface of the first shell layer, and improve the bonding tightness between the second shell layer and the first particle layer, thereby improving the stability and electronic conductivity of the lithium supplement material.

[0026] The particle size D50 of the MOF material is 5-15 nm, for example, 5 nm, 7 nm, 8 nm, 10 nm, 11 nm, 13 nm, 15 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] The present application adjusts the specific surface area of ​​the MOF material by adjusting the particle size of the MOF material, thereby improving the ability of the MOF material to capture carbon dioxide in the external environment and avoiding the reaction between the lithium supplement core and the carbon dioxide in the external environment.

[0028] In a third aspect, the present application provides a positive electrode sheet, which adopts the following technical solution:

[0029] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material, and the positive electrode material comprises the lithium supplement material as described above.

[0030] Preferably, the positive electrode material includes a positive electrode active material, a conductive agent, a binder and a lithium supplement material.

[0031] The lithium-supplementing material of the present application can alleviate the expansion of the active material in the positive electrode sheet during use, reduce the water absorption of the positive electrode active material containing the lithium-supplementing material, reduce the irreversible capacity loss of the positive electrode sheet during use, significantly improve the stability of the positive electrode sheet, and thus improve the cycle performance of the lithium battery.

[0032] Preferably, the mass proportion of the lithium supplement material in the positive electrode material is 0.5%-5%, for example, it can be 0.5%, 1%, 2%, 2.5%, 3%, 4%, 5%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] The lithium-supplementing material prepared in the present application has excellent electronic conductivity and long-term lithium-supplementing property, and has a lower mass proportion in the positive electrode active material than conventional lithium-supplementing materials in the art, thereby reducing costs.

[0034] In a fourth aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:

[0035] A method for preparing a lithium-ion battery, comprising a negative electrode sheet, a separator, an electrolyte and the positive electrode sheet as described above BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the particle structure of the lithium supplement material in this application.

[0037] In the figure: 1. lithium supplement core; 2. first shell; 3. second shell. DETAILED DESCRIPTION

[0038] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0040] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0041] As used herein, "and / or" means one or all of the mentioned elements.

[0042] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0043] All percentages in this application are by weight unless otherwise stated.

[0044] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0045] Example 1

[0046] 1. A lithium supplement material

[0047] The lithium supplement material in this embodiment is prepared by the following steps:

[0048] Step 1, lithium carbonate, iron phosphate and glucose are mixed in a molar ratio of lithium element: iron element: carbon element = 6:1:3.5, stirred, added with water, and ground to obtain a pre-ground slurry, wherein the particle size D50 of the particles in the pre-ground slurry is 0.8 μm;

[0049] Step 2, granulating the pre-ground slurry to obtain a first precursor;

[0050] Step 3, mixing a Nb-MOF material having a particle size D50 of 10 nm with ethanol to obtain a Nb-MOF slurry having a solid content of 5%, spraying the first precursor with the Nb-MOF slurry, and drying at 90° C. to obtain a second precursor;

[0051] Step 4: Place the second precursor in a calcining furnace and heat it at a rate of 6°C / min to 700°C and calcine at a constant temperature for 14 hours to obtain a lithium-supplementing material with a particle size D50 of 10 μm. The thickness of the first shell layer in the lithium-supplementing material is 5 nm, and the thickness of the second shell layer is 30 nm.

[0052] 2. Preparation of positive electrode

[0053] The positive electrode slurry is prepared as follows: lithium iron phosphate positive electrode active material, conductive agent acetylene black, binder PVDF, and the above-mentioned lithium supplement material are added to a vacuum mixer at a mass ratio of 96.5:0.5:1:2 for mixing, and then adding solvent NMP to the mixed slurry, and stirring the mixed slurry to a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment. The above-mentioned positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying, and after drying in the oven, a semi-finished positive electrode sheet is obtained, and then the semi-finished positive electrode sheet is cold pressed and cut to obtain the positive electrode sheet to be assembled.

[0054] 3. Preparation of negative electrode

[0055] The negative electrode slurry was prepared as follows: artificial graphite, conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer in a mass ratio of 96.4:1:1.2:1.4 for mixing, and then deionized water was added as a solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.

[0056] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.

[0057] 4. Preparation of lithium batteries

[0058] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 4.2V (charging upper limit) voltage system battery is used as an electrolyte. The above-mentioned positive electrode sheet, negative electrode sheet and separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.

[0059] Example 2

[0060] 1. A lithium supplement material

[0061] The lithium supplement material in this embodiment is prepared by the following steps:

[0062] Step 1, lithium nitrate, iron oxide and starch are mixed in a molar ratio of lithium element: iron element: carbon element = 5.5:1:4, stirred, added with water, and ground to obtain a pre-ground slurry, wherein the particle size D50 of the particles in the pre-ground slurry is 1.0 μm;

[0063] Step 2, granulating the pre-ground slurry to obtain a first precursor;

[0064] Step 3, mixing a Ti-MOF material having a particle size D50 of 5 nm with ethanol to obtain a Ti-MOF slurry having a solid content of 10%, spraying the first precursor with the Ti-MOF slurry, and drying at 105° C. to obtain a second precursor;

[0065] Step 4: Place the second precursor in a calcining furnace and heat it at a rate of 10°C / min to 500°C and calcine at a constant temperature for 18 hours to obtain a lithium-supplementing material with a particle size D50 of 5 μm. The thickness of the first shell layer in the lithium-supplementing material is 1.5 nm, and the thickness of the second shell layer is 10 nm.

[0066] 2. Preparation of positive electrode

[0067] The positive electrode slurry is prepared as follows: lithium iron phosphate positive electrode active material, conductive agent acetylene black, binder PVDF, and the above-mentioned lithium supplement material are added to a vacuum mixer at a mass ratio of 94:0.5:1:4.5 for mixing, and then the solvent NMP is added to the mixed slurry, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment. The above-mentioned positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying, and after drying in the oven, a semi-finished positive electrode sheet is obtained, and then the semi-finished positive electrode sheet is cold pressed and cut to obtain the positive electrode sheet to be assembled.

[0068] 3. Preparation of negative electrode

[0069] The preparation of the negative electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0070] 4 Preparation of lithium batteries

[0071] The preparation of the lithium battery in this embodiment is consistent with that in Embodiment 1.

[0072] Example 3

[0073] 1. A lithium supplement material

[0074] The lithium supplement material in this embodiment is prepared by the following steps:

[0075] Step 1, lithium acetate, ferrous sulfate and glucose are mixed in a molar ratio of lithium element: iron element: carbon element = 7:1:3, stirred, added with water, and ground to obtain a pre-ground slurry, wherein the particle size D50 of the particles in the pre-ground slurry is 0.2 μm;

[0076] Step 2, granulating the pre-ground slurry to obtain a first precursor;

[0077] Step 3, mixing a Mg-MOF material having a particle size D50 of 15 nm with ethanol to obtain a Mg-MOF slurry having a solid content of 1%, spraying the first precursor with the Mg-MOF slurry, and drying at 70° C. to obtain a second precursor;

[0078] Step 4: Place the second precursor in a calcining furnace and heat it at a rate of 2°C / min to 800°C and calcine at a constant temperature for 10 hours to obtain a lithium supplement material with a particle size D50 of 15 μm. The thickness of the first shell layer in the lithium supplement material is 10 nm, and the thickness of the second shell layer is 50 nm.

[0079] 2. Preparation of positive electrode

[0080] The positive electrode slurry is prepared as follows: lithium iron phosphate positive electrode active material, conductive agent acetylene black, binder PVDF, and the above-mentioned lithium supplement material are added to a vacuum mixer at a mass ratio of 96.5:1.5:1:1 for mixing, and then adding solvent NMP to the mixed slurry, and stirring the mixed slurry under the action of the vacuum mixer until it is uniform, thereby obtaining the positive electrode slurry of this embodiment. The above-mentioned positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying, and after drying in the oven, a semi-finished positive electrode sheet is obtained, and then the semi-finished positive electrode sheet is cold pressed and cut to obtain the positive electrode sheet to be assembled.

[0081] 3. Preparation of negative electrode

[0082] The preparation of the negative electrode sheet in this embodiment is consistent with that in Embodiment 1.

[0083] 4 Preparation of lithium batteries

[0084] The preparation of the lithium battery in this embodiment is consistent with that in Embodiment 1.

[0085] Example 4

[0086] The difference between this embodiment and embodiment 1 is that the particle size D50 of the lithium supplementing material is 2 μm; the other steps and parameter settings are consistent with those of embodiment 1.

[0087] Example 5

[0088] The difference between this embodiment and embodiment 1 is that the particle size D50 of the lithium supplementing material is 20 μm; the other steps and parameter settings are consistent with those of embodiment 1.

[0089] Example 6

[0090] The difference between this embodiment and embodiment 1 is that, in the process of preparing the lithium supplement material, the solid content of the MOF slurry used in step 3 is 0.3%; the rest is consistent with embodiment 1.

[0091] Example 7

[0092] The difference between this embodiment and embodiment 1 is that, in the process of preparing the lithium supplement material, the solid content of the MOF slurry used in step 3 is 13%; the rest is consistent with embodiment 1.

[0093] Example 8

[0094] The difference between this embodiment and embodiment 1 is that, in the process of preparing the lithium supplement material, the particle size D50 of the MOF material is 40 nm; the rest is consistent with embodiment 1.

[0095] Example 9

[0096] The difference between this embodiment and embodiment 1 is that the thickness of the first shell layer in the lithium supplement material is 0.1 nm; the other steps and parameter settings are consistent with those in embodiment 1.

[0097] Example 10

[0098] The difference between this embodiment and embodiment 1 is that the thickness of the second shell layer in the lithium supplementing material is 5 nm; the other steps and parameter settings are consistent with those in embodiment 1.

[0099] Comparative Example 1

[0100] The difference between this comparative example and Example 1 lies in the preparation of the lithium supplement material. The preparation steps of the lithium supplement material are as follows:

[0101] Step 1: Disperse lithium hydroxide and nickel sulfate in deionized water, and continue to add sucrose after they are completely dissolved to obtain a mixed solution, wherein the molar ratio of lithium element: iron element: carbon element in the mixed solution is 5.5-7:1:3-4;

[0102] Step 2: stirring the above solution at 80° C. to form a sol;

[0103] Step 3: Spray-dry the above sol to obtain a precursor powder, calcine the above precursor powder in an inert gas atmosphere for 10 hours, and cool the furnace to obtain a lithium-rich oxide Li2NiO2 / C with a core-shell structure having Li2NiO2 as a core and a carbon material as a shell. The particle size D50 of the lithium-rich oxide Li2NiO2 / C is 10 μm, and the shell thickness of the lithium-rich oxide Li2NiO2 / C is 50 nm.

[0104] Comparative Example 2

[0105] The difference between this comparative example and Example 1 is that the lithium supplement material only contains the second shell layer; the remaining steps and parameter settings are consistent with Example 1.

[0106] Comparative Example 3

[0107] The difference between this comparative example and Example 1 is that the lithium supplement material only contains the first shell layer; the remaining steps and parameter settings are consistent with Example 1.

[0108] Comparative Example 4

[0109] The difference between this comparative example and Example 1 is that, in the process of preparing the positive electrode sheet, an equal weight of conventional positive electrode lithium replenisher is used to replace the lithium replenishing material in Example 1; the remaining steps and parameter settings are consistent with Example 1.

[0110] Detection Methods

[0111] 1. Particle size test of lithium supplement materials

[0112] The particle size of the lithium supplement material prepared in the above embodiments and comparative examples was tested. The specific testing method is as follows: the powder particle size D50 and particle size concentration are tested by a Malvern laser particle size analyzer. D50 is the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, and the test data is recorded in Table 1.

[0113] 2. Coating thickness test

[0114] The thickness of the first shell layer and the second shell layer of the lithium supplement material prepared in the above embodiments and comparative examples was tested by TEM. The testing method is as follows: (1) The lithium supplement material samples prepared in the above embodiments and comparative examples were dispersed by ultrasonic vibration to remove soft agglomerates, and then dispersed in water or other solvents to prepare a sample suspension; (2) A copper mesh covered with a carbon film or other polymer film was taken, and the required amount was scooped out from the prepared sample suspension or sucked with a dropper, and dropped onto the copper mesh. After being sucked dry with filter paper or air-dried, the sample was placed on a sample table for testing; (3) On a representative and size-distributed surface, the sample suspension was measured. The narrow places and the well-dispersed places are photographed, and the lithium-supplementing materials with complete morphology are arbitrarily selected to measure the size; after the pre-ground slurry is dried, the particles therein are tested by TEM to measure the size of the core of the lithium-supplementing material and recorded as d1; after the first precursor is obtained, the size of the first precursor is measured by TEM test and recorded as d2, and after the lithium-supplementing material is obtained, the size of the lithium-supplementing material is measured by TEM test and recorded as d3; then, the calculation formula for the thickness h1 of the first shell layer is: h1=d2-d1, and the calculation formula for the thickness h2 of the second shell layer is: h2=d3-d2.

[0115] 3. Lithium battery energy density test

[0116] The energy density test of the ion batteries prepared in the above examples and comparative examples was carried out according to the national standard GB / T31486-2015 "Electrical Performance Requirements and Test Methods for Power Batteries for Electric Vehicles".

[0117] 4. Lithium battery cycle performance test

[0118] The lithium ion batteries prepared in the above embodiments and comparative examples were placed in an oven at a constant temperature of 25°C, charged to 4.20V at a constant current of 1C, then the constant voltage charging current was reduced to 0.05C, left to stand for 10 minutes, and then discharged to 2.5V at a constant current of 1C, and cycled until the capacity was less than 80% of the initial capacity (cycle cutoff condition), and the number of cycles at this time was recorded in Table 1.

[0119] Table 1

[0120]

[0121]

[0122] In combination with Examples 1-3, Comparative Examples 1-4 and Table 1, it can be seen that the lithium-supplementing material with a double-layer core-shell structure prepared in the present application can significantly improve the energy density and cycle performance of the lithium battery after being added to the positive electrode active material; this is because the lithium-supplementing material of the present application can isolate carbon dioxide and water in the external environment, improve the stability of the lithium-supplementing material, and avoid the residual alkali therein reacting with carbon dioxide and water to cause gel to appear in the positive electrode active material, affecting the adhesion stability of the positive electrode active material on the surface of the positive electrode current collector, so that the lithium-supplementing material can exert the lithium-supplementing performance for a long time, and improve the energy density and cycle performance of the lithium battery; and the core-shell structure of the present application can construct a pore structure that is convenient for ions and electrons to pass through, significantly improve the electronic conductivity of the lithium-supplementing material, and further improve the cycle performance of the lithium battery.

[0123] Combining Examples 1, 4-5 and Table 1, it can be seen that when the particle size of the lithium supplement material is too large or too small, the cycle performance of the lithium battery is slightly reduced; this is because, when the particle size of the lithium supplement material is too small, the lithium supplement material is easy to agglomerate in the positive electrode active material, and the thickness of the first shell layer and the second shell layer is uneven, which is not conducive to the construction of a conductive network structure uniformly distributed on the surface of the lithium supplement agent core. When the particle size of the lithium supplement material is too large, the migration path of ions and electrons is increased, and the internal resistance of the lithium battery is increased, which is not conducive to the improvement of the cycle performance of the lithium battery.

[0124] In combination with Examples 1, 6-8 and Table 1, it can be seen that when the solid content of the MOF slurry is too low or too high, and the particle size D50 of the MOF material is too large, the cycle performance of the lithium battery decreases slightly. This is because when the solid content of the MOF slurry is too high or too low, and the particle size D50 of the MOF material is too large, it is not conducive to the formation of a second shell layer with uniform thickness, which affects the pore structure of the MOF material in the second shell layer, is not conducive to the conduction of ions and electrons, and thus reduces the cycle performance of the lithium battery.

[0125] Combining Examples 1, 9-10 and Table 1, it can be seen that when the thickness of the first shell layer is too small, the degree of bonding between the second shell layer and the first shell layer is low, which is not conducive to the coating stability of the shell structure and affects the cycle stability of the lithium battery; and when the thickness of the second shell layer is too small, it will be not conducive to improving the electronic conduction of the lithium supplement material and reduce the electrochemical performance of the lithium battery.

[0126] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lithium supplement material, characterized in that: It comprises a lithium supplement core and a first shell layer and a second shell layer which are sequentially arranged on a surface away from the lithium supplement core; the first shell layer comprises a carbon material, and the second shell layer comprises an MOF material.

2. A lithium supplement material according to claim 1, characterized in that: The particle size D50 of the lithium supplement material is 5-15 μm.

3. A lithium supplement material according to claim 1, characterized in that: The thickness of the first shell layer is 1-10 nm.

4. A lithium supplement material according to claim 1, characterized in that: The thickness of the second shell layer is 10-50 nm.

5. A lithium supplement material according to claim 1, characterized in that: The MOF material includes any one of Al-MOF, Nb-MOF, Ti-MOF and Mg-MOF.

6. A lithium supplement material according to claim 1, characterized in that: The lithium supplement core includes at least one of lithium-rich lithium iron oxide, lithium-rich lithium nickel oxide, lithium-rich manganese nickel oxide, and lithium-rich nickel iron oxide.

7. The method for preparing the lithium supplement material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, mixing a lithium source, an iron source and a carbon source, adding water, and grinding to obtain a pre-ground slurry; Step 2, granulating the pre-ground slurry to obtain a first precursor; Step 3, spraying the first precursor with the atomized MOF material, and drying to obtain a second precursor; Step 4: calcining the second precursor to obtain the lithium supplement material.

8. The method for preparing a lithium supplement material according to claim 7, characterized in that: In the step three, the preparation of the atomized MOF material comprises the following steps: the MOF material and ethanol are mixed and then ground to obtain MOF slurry, wherein the solid content of the MOF slurry is 1%-10%.

9. The method for preparing a lithium supplement material according to claim 8, characterized in that: The particle size D50 of the MOF material is 5-15 nm.

10. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer located on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material, and the positive electrode material comprises the lithium supplement material as claimed in any one of claims 1 to 9.

11. A positive electrode sheet according to claim 10, characterized in that: The mass proportion of the lithium supplement material in the positive electrode material is 0.5%-5%.

12. A lithium ion battery, characterized in that: The invention comprises a negative electrode sheet, a separator, an electrolyte and a positive electrode sheet as claimed in any one of claims 10 to 11.

Citation Information

Patent Citations

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN114709421A

  • Preparation method of carbon-coated lithium-rich lithium ferrite as well as obtained product and application of carbon-coated lithium-rich lithium ferrite

    CN115642232A

  • Lithium supplement material and preparation method thereof, positive pole piece and secondary battery

    CN116470058A

  • Lithium supplement material precursor, lithium supplement material and preparation method and application of lithium supplement material

    CN116730393A

  • Lithium supplement material and preparation method thereof, positive electrode material and secondary battery

    CN117638079A

Cited By

  • Lithium-replenishing material, preparation method therefor, and use thereof

    WO2026137658A1